PENGEMBANGAN BOOKLET KEANEKARAGAMAN JENIS TUMBUHAN ANGIOSPERMAE KELAS MAGNOLIOPSIDA (DICOTYLEDONEAE) SEBAGAI SUMBER BELAJAR BIOLOGI MATERI PLANTAE - Widya Muslimawati , Ade; Karim , Hilda; Muis, Abd (Universitas Cokroaminoto Palopo, 2023)
The booklet on the diversity of species of magnoliopsida (dicotyledoneae) class of angiosperm plants is one of the learning resources that can be used to help students in the learning process. The purpose of this study was to develop a booklet as a valid learning resource for class X high school plantae material. This research was conducted at the Department of Biology FMIPA UNM. This development research uses the ADDIE development model which has five stages namely analysis, design, development, implementation, and evaluation. Product development begins with designing a booklet on the Canva application and then printing it for further evaluation by expert validators. The results showed that the developed booklet had a validity level of 4.67. So it can be concluded that the magnoliopsida (dicotyledoneae) class diversity booklet of angiosperm plant species as a source of biology learning material for class X high school plantae is very valid.